Reversible Changes in BDNF Expression in MK-801-Induced Hippocampal Astrocytes Through NMDAR/PI3K/ERK Signaling - Yu, Wenjuan; Fang, Hongwei; Zhang, Lei; Hu, Miaowen; He, Sidi; Li, Huafang; Zhu, Hao (Frontiers in Cellular Neuroscience, 2021)
Dizocilpine (MK-801), a non-competitive N-methyl-D-aspartic acid receptor (NMDA-R) antagonist, can induce schizophrenia-like symptoms in healthy individuals, implicating NMDA-R hypofunction in disease pathogenesis. Brain-derived neurotrophic factor (BDNF) is also implicated in schizophrenia, and expression is regulated by NMDA-R activity, suggesting a functional link. We previously found that BDNF signaling was upregulated by MK-801 in cultured hippocampal astrocytes, but the underlying mechanism is not clear. To address this issue, the levels of BDNF expression and secretion were evaluated in hippocampal astrocytes incubated with MK-801 by ELISA and real-time PCR, with and without NMDA co-incubation or pretreatment of either the ERK1/2 inhibitor, PD98059 or the PI3K inhibitor, LY294002. The apoptosis, viability, and proliferation of the astrocytes were also examined. In the current study, we demonstrate that MK-801 treatment (20 M for 5 days) enhances the proliferation of rat cultured hippocampal astrocytes. Expression of BDNF mRNA was enhanced after 24 h in MK-801, but returned to near baseline over the next 24 h in the continued presence of MK-801. However, two successive 24-h treatments enhanced BDNF expression. These application regimens had no effect on apoptosis or proliferation rate. Co-addition of NMDA significantly inhibited MK-801-induced upregulation of BDNF. Similarly, MK-801-induced BDNF upregulation was blocked by pretreatment with inhibitors of PI3K and ERK1/2, but not by inhibitors of p38 and JNK. These findings suggested that astrocytes may contribute to the acute neurological and behavioral response to MK-801 treatment via a transient increase in BDNF expression involving NMDA-R–PI3K–ERK signaling.